sj-docx-1-css-10.1177_24705470221128004 - Supplemental material for Proton Magnetic Resonance Spectroscopy in Post-Traumatic Stress Disorder—Updated Systematic Review and Meta-Analysis - Kelley M. Swanberg; Leonardo Campos; Chadi G. Abdallah; Christoph Juchem (SAGE Journals, 2022)
Supplemental material, sj-docx-1-css-10.1177_24705470221128004 for Proton Magnetic Resonance Spectroscopy in Post-Traumatic Stress Disorder—Updated Systematic Review and Meta-Analysis by Kelley M. Swanberg, Leonardo Campos, Chadi G. Abdallah and Christoph Juchem in Chronic Stress
Keywords: 110904 Neurology and Neuromuscular Diseases; 170199 Psychology not elsewhere classified; 110319 Psychiatry (incl. Psychotherapy); 111799 Public Health and Health Services not elsewhere classified